'Scientific Strabismus' or two related pandemics: coronavirus disease and vitamin D deficiency. Issue 7 (14th October 2020) - Kara, Murat; Ekiz, Timur; Ricci, Vincenzo; Kara, Özgür; Chang, Ke-Vin; Özçakar, Levent
Abstract : Abstract: The WHO has announced the novel coronavirus disease (COVID-19) outbreak to be a global pandemic. The distribution of community outbreaks shows seasonal patterns along certain latitude, temperature and humidity, that is, similar to the behaviour of seasonal viral respiratory tract infections. COVID-19 displays significant spread in northern mid-latitude countries with an average temperature of 5–11°C and low humidity. Vitamin D deficiency has also been described as pandemic, especially in Europe. Regardless of age, ethnicity and latitude, recent data showed that 40 % of Europeans are vitamin D deficient (25-hydroxyvitamin D (25(OH)D) levels <50 nmol/l), and 13 % are severely deficient (25(OH)D < 30 nmol/l). A quadratic relationship was found between the prevalences of vitamin D deficiency in most commonly affected countries by COVID-19 and the latitudes. Vitamin D deficiency is more common in the subtropical and mid-latitude countries than the tropical and high-latitude countries. The most commonly affected countries with severe vitamin D deficiency are from the subtropical (Saudi Arabia 46 %; Qatar 46 %; Iran 33·4 %; Chile 26·4 %) and mid-latitude (France 27·3 %; Portugal 21·2 %; Austria 19·3 %) regions. Severe vitamin D deficiency was found to be nearly 0 % in some high-latitude countries (e.g. Norway, Finland, Sweden, Denmark and Netherlands). Accordingly, we would like to call attention to the possible association between severe vitamin D deficiency and mortality pertaining to COVID-19. Given its rare side effects and relatively wide safety, prophylactic vitamin D supplementation and/or food fortification might reasonably serve as a very convenient adjuvant therapy for these two worldwide public health problems alike.